Supramolecular spheres assembled from covalent and supramolecular dendritic crowns dictate the supramolecular orientational memory effect mediated by Frank–Kasper phases. (March 2020) - Huang, Ning; Imam, Mohammad R.; Sienkowska, Monika J.; Peterca, Mihai; Holerca, Marian N.; Wilson, Daniela A.; Rosen, Brad M.; Partridge, Benjamin E.; Xiao, Qi; Percec, Virgil
Highlights: Supramolecular spheres assembled from conical shape dendrons do not show SOM. Supramolecular spheres assembled from crown shape dendrimers exhibit SOM. Covalent and dynamic supramolecular crowns display different SOM architectures. A new distorted dodecahedral architecture of hexagonal columns was induced by SOM. SOM discriminates between mechanisms of self-assembly of supramolecular spheres. Abstract: A supramolecular orientational memory (SOM) effect that provides access to complex columnar hexagonal architectures that cannot be designed by any other methodology was recently reported by our laboratory. This SOM concept is encountered upon heating and cooling a hexagonal columnar periodic array via a Frank–Kasper phase that is generated from supramolecular spheres. Here, a library of twenty-four supramolecular spheres self-organizing into Frank–Kasper phases and columnar hexagonal arrays was investigated for SOM. Twenty of these supramolecular spheres, that were self-assembled from conical shaped dendrons, did not exhibit SOM. The four supramolecular spheres assembled from covalent and supramolecular dynamic crowns displayed SOM. The supramolecular dynamic crowns forming spheres by a strong and directional H-bonding process, generated via SOM, a previously unencountered distorted dodecahedral architecture constructed from hexagonally ordered supramolecular columns. Therefore, SOM can discriminate between mechanisms of self-assembly of supramolecular spheres, a process that cannot be accomplished by analysis with X-ray diffraction methods alone. These results will facilitate access to the design of new complex columnar hexagonal and other periodic columnar array architectures via SOM. Graphical abstract: Image, graphical abstract